PENGARUH LITERASI DIGITAL TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR KOTA MAKASSAR: BAHASA INDONESIA DAN BAHASA INGGRIS - Mendi_Tutut Arima; Nurhadifah Amaliyah; Perawati Abustang; Syamsul Alam (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to determine the effect of digital literacy on student learning outcomes at SD Inpres Bangkala III Makassar City. This research is classified into the type of Ex Post Facto research using a quantitative approach. This research was conducted at SD Inpres Bangkala III Makassar City. The sample of this study were all students of class VA SD Inpres Bangkala III Makassar City. Which consisted of 30 students. The total number of samples used is 30 students, using non-random sampling technique. The results of this study using descriptive analysis, the average value of digital literacy is 70.10 which is in the good category and the value of learning outcomes is 82.63 which is in the good category. Inferential analysis, the results of the digital literacy normality test are 0.327 and the learning outcomes are 0.248 > 0.05 (normality distributed), the homogenity test results are 0.114 > 0.05 (homogenity), the linearity test results are 0.080 > 0.05 based on the data results, there is a relationship which is linear digital literacy on learning outcomes. The results of the hypothesis test showed a sig value of 0.003, with the criteria of sig (0.003) < α (0.05). The conclusion in this study is that there is an influence of digital literacy on student learning outcomes of SD Inpres Bangkala III Makassar City.